Analysis of the Implementation Study of Law No. 6 of 2023 Concerning Worker Protection Policies: A Case Study in Semarang City, Indonesia - Rafsanjani, Akbar (HM Publisher, 2024)
Law No. 6 of 2023 concerning Job Creation (Job Creation Law) brings significant changes to employment policy in Indonesia, including labor protection. This research aims to analyze the implementation of the Job Creation Law regarding worker protection in Semarang City through a qualitative study. This research uses a qualitative approach with a case study method. Data was collected through in-depth interviews with 20 workers in Semarang City from various industrial sectors, as well as analysis of related documents. Data analysis was carried out thematically to identify the main themes related to the implementation of the Job Creation Law. The research results show that the implementation of the Job Creation Law regarding worker protection in Semarang City still faces challenges. Some of the main findings include: (1) A lack of understanding regarding regulatory changes among the workforce, (2) Inadequate socialization and education regarding the Job Creation Law, (3) Concerns regarding the potential negative impact of the Job Creation Law on workers' rights, and (4) the need to increase capacity and supervision on the part of the government and trade unions. Implementation of the Job Creation Law regarding worker protection in Semarang City requires further efforts from various parties. Increasing understanding, socialization, and education regarding the Job Creation Law is crucial. In addition, it is important to strengthen supervision and law enforcement to ensure the protection of workers' rights in accordance with the mandate of the Job Creation Law.